Gender differences in overeducation: A test of the theory of differential overqualification - Robst, John; McGoldrick, KimMarie (American Economic Review, 1996)
There is little question that substantial labormarket differences exist between men and women. Among the most researched difference is the male-female wage gap. Many different theories are used to explain why men earn more than women. One possible reason is based on the limited geographic mobility of married women (Robert Frank, 1978). Family mobility is a joint decision in which the needs of the husband and wife are balanced to maximize family welfare. Job-motivated relocations are generally made to benefit the primary earner in the family. This leads to a constrained job search for the secondary earner, as he or she must search for a job in a limited geographic area. Since the husband is still the primary wage earner in many families, the job search of the wife may suffer. Individuals who are tied to a certain area are labeled tied-stayers, while secondary earners who move for the benefit of the family are labeled tied-movers (Jacob Mincer, 1978). The wages of a tied-stayer or tied-mover may not be substantially lower if the family lives in or moves to a large city. If a large labor market has more vacancies, the wife may locate a wage offer near the maximum she would find with a nationwide job search. However, being a tied-stayer or tied-mover can lower the wife's wage if the family lives in or moves to a small community. A small labor market will reduce the likelihood of her finding a job that utilizes her skills. As a result she may accept a job for which she is overqualified and thus earn a lower wage.' This hypothesized relationship between the likelihood of being overqualified and SMSA size is termed overqualification. Frank ( 1978) and Haim Ofek and Yesook Merrill (1994) provide support for the theory of differential overqualification by finding that the malefemale wage gap is greater in smaller SMSA's. While the results are consistent with the existence of differential overqualification, they may also result from other situations as well. Firms in small labor markets may use their monopsony power to keep wages down.2 Local demand shocks are found to be a major source of wage variation both across and within local labor markets (Robert Topel, 1986). Since large labor markets are generally more diversified, a demand shock can have a substantial impact on immobile workers in small labor markets. Another reason for examining differential overqualification involves the assumption that there are more vacancies in large labor markets. While there is little doubt that more vacancies exist in large labor markets, there are also likely to be more people searching for jobs in large labor markets. If the greater number of vacancies is offset by the larger number of searchers, it is unclear whether women will be more likely to be overqualified in small labor markets. Instead of relying on wages to determine if differential overqualification exists, we consider an explicit form of overqualification based on education.